Anomalous origin of the left coronary artery from the pulmonary artery with coronary artery steal in adults. Report of two cases and review of the literature. Issue 3 (June 1976) - Ihekwaba, F N; Davidson, K G; Ogilvie, B; Caves, P K
Abstract : Patients with anomalous left coronary artery arising from the pulmonary artery rarely survive to adult life. Those who attain adulthood may present with angina indistinguishable from coronary artery disease and are liable to sudden death. Myocardial infarction, though rare in young adults, may occur and may be due to coronary artery steal. Accurate diagnosis requires coronary arteriography. Two further cases of coronary artery steal in adults with anomalous origin of the left coronary artery from the pulmonary artery are presented. In both patients aortocoronary bypass grafting using a reversed autogenous saphenous vein with closure of the origin of the anomalous left coronary artery was successfully performed. This operation provided complete symptomatic relief and may protect patients against the risk of sudden death.